Analisis Produktivitas Kerja Petani Tambak Dalam Pembudidayaan Udang Windu di Kota Medan - Karimuddin Karimuddin; Rahmanta Ginting; Syaifuddin Lubis (JURNAL AGRICA, 2018)
The study was conducted at the Labuhan Deli Village, Medan Marelan District which is one of the shrimp farming locations at the Medan City, starts from April to May 2008. The purpose of research is to analyze how the effect of work ability, work motivation and support work on the productivity of farmers in the cultivation of shrimp ponds at the Medan City. The study used descriptive method through surveys. The data analyzed by multiple regression models of Ordinary Least Square (OLS) and developed with path analysis to determine the work ability, work motivation and support work affect the work productivity. The data used are primary data by research and secondary data from reports of the Marine Fisheries Service of Medan City, the Department of Marine and Fisheries and from other sources related to this thesis. To determine the relationship between work ability, work motivation and support employment of labor productivity simultanously by F-test, while partially by t-test. The number of fish farmers as respondents was 35 from 40 populations taken by simple random sampling. Instruments used to collect data by questionnaire with a scoring system number 1 to number 5 (Likert Scale). The results showed that the variables work ability, work motivation and support work simultanously had a positively and significant effect on labor productivity, that’s mean that if the work ability, work motivation and support improved simultan then the labor productivity of fish farmer will increase significantly. Partially, the ability to work and the work motivation had a significantly effect on labor productivity. Keywords : productivity, of ordinary least square (OLS), tiger shrimp